Behavior of Swelling Soils Saturated with Magnetized Water - Muhauwiss, Farouk M.; AL–Faoury, Ahmed A. E. (International Journal of Engineering and Technology, 2018)
This paper presents an experimental study on the behavior of swelling soils saturated with magnetized water. Parameters investigated were free swelling and swelling pressure of clayey soil saturated in magnetized water with four magnetic intensities (500, 1000, 1500, and 2000). Three specimens (extracted from three different locations in Iraq) were tested in different magnetic intensities and compared with a soil specimen saturated with ordinary water. Magnetized water was produced by passing water through a P.V.C. pipe bounded with a magnetic field. It was found that the value of swelling pressure and free swelling (of the soils saturated with magnetized water) increase with the increase of magnetic intensities. In specific, the value of free swelling and swelling pressure ranging between 26.38% - 59.0 % and 32.16% - 161.16%, respectively.